Toxic effects of herbal medicines: Teucrium polium and acute kidney injury - Aktürk Esen, Selin; Kahvecioğlu, Serdar; Gül, Cuma Bülent; Aktaş, Nimet; Esen, İrfan (The European Research Journal, 2019)
Herbal medicines are believed to be effective in the treatment of many diseases. The genius Teucrium is a member of Lamiaceae family, which contains more than 300 species. Antimutagenic, anticancer, hypoglycemic, antibacterial, anti-inflammatory, antipyretic, antiulcer, hypolipidemic and antidiarrheal effects of Teucrium polium have been reported in the studies. In this article, we describe an acute kidney injury (AKI), which is thought to have developed as a result of T. polium use for the treatment of diabetes mellitus. It should not be forgotten that herbal medicine is an important reason for AKI. In addition, community should be made aware of the danger of herbal medicines which especially have potential renal and hepatic side effects.